2012
DOI: 10.1002/cne.23004
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin β4 induces folding of the developing optic tectum in the chicken (Gallus domesticus)

Abstract: Thymosin β4 (Tβ4) is a highly conserved G-actin binding polypeptide with multiple intra- and extracellular functions. While stem-cell activation as well as promotion of cell survival and migration by Tβ4 have been investigated in various in vitro and in vivo studies, there are few data on the implications of Tβ4 in brain development. In the present study we analyzed Tβ4 expression in the developing optic tectum of the chicken (Gallus domesticus) and performed in ovo retroviral transduction and plasmid electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
(65 reference statements)
1
6
0
Order By: Relevance
“…The manufacturer tested the specificity of this antibody by western blot and found that it recognized a single band of 17KDa in colchemid-arrested HeLa cells as predicted. This antibody has been reported to detect mitotic cells in several species, including the optic tectum of chick, fish, and xenopus where staining is concentrated in mitotically active nuclei that line the ventricular layer of the tectum, similar to the expression we report (Schmidt and Derby, 2011; Tibber et al, 2006; Wirsching et al, 2012). We found that the antibody labels select nuclei in the Xenopus tadpole tectal proliferative zone that display morphological features of nuclei in various phases of mitosis.…”
Section: Methodssupporting
confidence: 84%
“…The manufacturer tested the specificity of this antibody by western blot and found that it recognized a single band of 17KDa in colchemid-arrested HeLa cells as predicted. This antibody has been reported to detect mitotic cells in several species, including the optic tectum of chick, fish, and xenopus where staining is concentrated in mitotically active nuclei that line the ventricular layer of the tectum, similar to the expression we report (Schmidt and Derby, 2011; Tibber et al, 2006; Wirsching et al, 2012). We found that the antibody labels select nuclei in the Xenopus tadpole tectal proliferative zone that display morphological features of nuclei in various phases of mitosis.…”
Section: Methodssupporting
confidence: 84%
“…Cells grown on sterile glass coverslips in DMEM (Dulbecco modified Eagle medium) with added NCS (neonatal calf serum) and FCS were fixed with 4% formaldehyde for 20 min, permeabilized with 0.2% Triton X‐100 in PBS (phosphate buffered saline) for 5–10 min or alternatively fixed with ice cold methanol for 5 min and subsequently washed three times in PBS. Cell transfection was performed using vector‐coated magnetic beads (MATra, IBA, Göttingen, Germany) using the EGFP‐expressing vector and the Tβ4‐pIRES2‐EGFP constructs described previously [Mannherz et al, ; Lai et al, ; Wirsching et al, ]. For Tβ4 knockdown we used Tβ4‐specific siRNAs as described [Wirsching et al, ], which were selected to target the following sequences of the human Tβ4 mRNA (accession code TMSB4X) starting from position 103 (GAGATCGAGAAATTCGATA), 195 (GCAAGCAGGCGAATCGTAA), 472 (GACGACAGTGAAATCTAGA), or 526 (GTAATGCAGTTTAATCAGA).…”
Section: Methodsmentioning
confidence: 99%
“…Tβ4 is the major G-actin-sequestering molecule, and its primary physiological function is to regulate cell motility (Bock-Marquette et al, 2004). During (Chopp and Zhang, 2015;Kuzan, 2016;Goldstein and Kleinman, 2015) THYMOSIN-β10 (Tβ−10) rat, mice, humans, cattle, cytoskeleton organization and morphology, proliferation, motility, anti-inflammatory effects, insulin secretion (Sribenja et al, 2009;Zhang et al, 2017b) THYMOSIN-β15 (Tβ−15) rat, mice, human motility, progression and metastatis of non-small cell lung cancer (Banyard et al, 2007) development of CNS, Tβ4 regulates neurogenesis, tangential expansion, tissue growth and hemisphere folding (Lever et al, 2017;Wirsching et al, 2012Wirsching et al, , 2014. Tβ4 was initially employed as an anti-inflammatory agent (Badamchian et al, 2003;Girardi et al, 2003) and, subsequently, to inhibit proliferation and induce differentiation and apoptosis of leukemic cells (Huang et al, 2006).…”
Section: Thymosins: the Old And The Newmentioning
confidence: 99%